2014
DOI: 10.1155/2014/213013
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofVetiveria zizanioidesEssential Oil on Melanogenesis in Melanoma Cells: Downregulation of Tyrosinase Expression and Suppression of Oxidative Stress

Abstract: The major objective of this study was to estimate the hypopigmentation function of the essential oil from Vetiveria zizanioides (VZ-EO). Our results indicated that VZ-EO exhibits potent lipid peroxidation inhibitory activity to moderate the bleaching of β-carotene and to maintain the cellular glutathione (GSH) levels. VZ-EO can markedly decrease melanin production and tyrosinase activity in α-melanin-stimulating-hormone- (α-MSH-) stimulated B16 cells. The effect of VZ-EO on melanogenesis is achieved by the sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…EOs ability to inhibit this enzyme has been reported as competitive, non-competitive or mixed, based on their chemical composition [96]. Due to the complexity of the EO compositions, this activity is most probably attributable to a synergistic interaction of their compounds with the enzyme, rather than to a single component [97,98]. Contrary to published reports [96,99], however, the anti-tyrosinase activity does not seem correlated to the oxygenated monoterpenes fraction in the EOs composition: the two best performing ones in our assay were, indeed, the EOs with the lowest relative abundances of this chemical class of compounds.…”
Section: Discussionmentioning
confidence: 99%
“…EOs ability to inhibit this enzyme has been reported as competitive, non-competitive or mixed, based on their chemical composition [96]. Due to the complexity of the EO compositions, this activity is most probably attributable to a synergistic interaction of their compounds with the enzyme, rather than to a single component [97,98]. Contrary to published reports [96,99], however, the anti-tyrosinase activity does not seem correlated to the oxygenated monoterpenes fraction in the EOs composition: the two best performing ones in our assay were, indeed, the EOs with the lowest relative abundances of this chemical class of compounds.…”
Section: Discussionmentioning
confidence: 99%
“…For western blotting, each well was loaded with 20 ng of protein and resolved by 10% SDS PAGE and then electro-transferred on to a polyvinylidene difluoride (PVDF) membrane using the Bio-Rad MiniProtean II apparatus (Bio-Rad Laboratories, Carlsbad, CA, USA). The blots were then incubated with an anti-MITF, anti-tyrosinase or anti-GAPDH antibody as the primary antibody, and the immune complexes were visualized using an ECL reagent (Millipore, Billerica, MA, USA) [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that VZ-EO exhibits significant antioxidant activity and suppresses the β-MSH-induced melanogenesis thereby decreasing melanin production through tyrosinase inactivation and the simultaneous suppression of oxidative stress in B16 melanoma cells. [ 64 ] Therefore, VZ-EO has the potential to become an ingredient in future hypopigmentation cosmetics.…”
Section: Methodsmentioning
confidence: 99%